Trichloroethylene-alcohol-water solubility characteristics with implications for partitioning tracer tests at DNAPL contaminated sites - A. Putthividhya; K. Manajit (International Association of Lowland Technology, 2017)
Dense nonaqueous phase liquids (DNAPLs) widely occurred at numerous subsurface sites can act as long-term sources of both vapor-phase and groundwater contamination. Successful remediation and effective risk assessment of DNAPLcontaminated sites is limited by current source zone characterization techniques and DNAPL unique behavior. A relatively new method of DNAPL-contaminated site characterization involved the use of partitioning tracers to provide estimates of the known amount of DNAPL. A new practical continuous flow system was developed in this work to explore the DNAPL’s partitioning tracer-water solubility characteristics under pure phase and selected cosolvents conditions which can be crucial for estimate retardation factors of various tracers with implications for partitioning tracer tests at DNAPL-contaminated sites. Trichloroethylene (TCE) was selected as a representative of DNAPL due to its unique properties and solvent effects. Bromide was employed as a non-partitioning tracer, while three alcohols (i.e., iso-propanol, methanol, and ethanol) effluents were determined as a function of time under pure solvent and 30% cosolvent additions. The three alcohols appeared to have been used successfully as a partitioning tracers for detection of potential DNAPL saturation. Moment analysis of breakthrough curves allowed TCE and alcohol mass recovery and retardation factor calculation, and therefore could further estimate apparent DNAPL saturation. Assuming that partitioning to TCE-DNAPL is the only mechanism for retention of alcohols in the system, flow rate and various alcohol fraction additions seemed to have no major influence on retardation factor estimation of partitioning tracers in the system.